Surgical treatment of multifragmentary segmental femur shaft fractures with ORIF and bone graft versus MIPO: a prospective control-group study - Giuseppe Rollo; Mario Ronga; Enrico Maria Bonura; Rocco Erasmo; Michele Bisaccia; Paolo Pichierri; Antonio Marsilio; Andrea Pasquino; David Gomez Garrido; Raffaele Franzese; Andrea Schiavone; Luigi Meccariello (Medicinski glasnik, 2020)
Aim: Multifragmentary segmental femoral shaft fracture is a high energy injury frequently associated with life-threatening conditions. The aim of this study was to compare the use of bio metallic open reduction internal fixation (ORIF) (plate with allograft bone strut) with minimally invasive plate osteosynthesis (MIPO) fixation for the treatment of multi-segmental femoral shaft fracture in terms of outcomes, bone healing and complications. Methods: Forty patients with segmental femoral shaft fractures were included and divided into two groups: 20 patients treated with ORIF+, 20 with MIPO. All fractures were classified according to AO (Arbeitsgemeinschaft für Osteosynthesefragen) and Winquist and Hansen Classification. Evaluation criteria were: duration of follow up and surgery, Non-Union Scoring System, Pain Visual Analogic Scale (VAS), objective quality of life and hip function, subjective quality of life and knee function, quality of life the Short Form-12 Survey Questionnaires (SF-12), bone healing and femoral alignment (radiographs), Radiographic Union Score for Hip (RUSH). Results: Better results of ORIF in terms of complication rate, RUSH, VAS, regression between RUSH and VAS, average correlation clinical-radiographic results and patients' outcomes (Cohen k) were obtained, and similar results for the length of follow up, surgery duration, perioperative blood transfusion, wound healing. No statistical difference for Harris Hip Score (HHS), Knee Society Score (KSS), quality of life (SF-12). Conclusions: The ORIF and bone strut allograft technique had better results compared to the MIPO technique with regards to complication rate, RUSH, VAS, regression between RUSH and VAS, and average correlation clinical-radiographic results and patients' outcomes (Cohen k) in the surgical treatment of multifragmentary segmental femoral shaft fractures.
Keywords: allograft; bone strut; limb reconstruction; trauma; outcomes